Proceedings of the 2019 International Conference on Organizational Innovation (ICOI 2019) 2019
DOI: 10.2991/icoi-19.2019.105
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Efficacy and Social Media towards the Interest of Social Entrepreneurs on Cadres of Posyandu (Maternal and Child Health Services) in Medan Labuhan Sub-district

Abstract: This research aims to demonstrate the influence of self-efficacy and social media towards the interest of social entrepreneurs on cadres of posyandu (maternal and child health services) in Medan Labuhan sub-district. The focus of this research are the cadres of posyandu in Medan Labuhan sub-district. It is hoped that it will encourage social entrepreneurship in Medan Labuhan sub-district that will increase the income of the community and cadres of posyandu in Medan Labuhan. The research methods used in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To become entrepreneurs, students also need to have high self-efficacy, which is related to the belief in his/her abilities (Aslam & Hasnu, 2016) and, consequently, determines their way of thinking, persistence in action, and ability to motivate themselves when facing difficulties (Asmara et al, 2016). Dalimunthe et al (2019) also revealed that self-efficacy greatly affects students' motivation to achieve success or goals. In other words, high self-efficacy is associated with increased expectations, goals, and work-related performance (Cassar & Friedman, 2009).…”
Section: Findings and Discussion Validity And Reliability Test Resultsmentioning
confidence: 99%
“…To become entrepreneurs, students also need to have high self-efficacy, which is related to the belief in his/her abilities (Aslam & Hasnu, 2016) and, consequently, determines their way of thinking, persistence in action, and ability to motivate themselves when facing difficulties (Asmara et al, 2016). Dalimunthe et al (2019) also revealed that self-efficacy greatly affects students' motivation to achieve success or goals. In other words, high self-efficacy is associated with increased expectations, goals, and work-related performance (Cassar & Friedman, 2009).…”
Section: Findings and Discussion Validity And Reliability Test Resultsmentioning
confidence: 99%
“…The generality dimension, associated with confidence in various situations, had a moderate average score. This dimension encompasses beliefs in the breadth of the behavioral domain and whether there are limitations to one's confidence in abilities in specific situations or activities (Dalimunthe & Ramadini, 2019;Darwanty et al, 2023;Hanifah, n.d.).…”
Section: Discussionmentioning
confidence: 99%